Natural Resource Abundance, Growth, and Diversification in the Middle East and North Africa : The Effects of Natural Resources and the Role of Policies - Diop, Ndiamé; Marotta, Daniela; de Melo, Jaime (Washington, DC: World Bank, 2012)
This book is organized as follows: this first chapter examines the pattern of structural transformation in Middle East and North Africa, or MENA and summarizes the role of various factors examined thoroughly in the rest of the volume. This second chapter examines the correlates of this overall disappointing performance. At the macro level, MENA countries have been unable to maintain depreciated (undervalued) real exchange rates for long periods, yet such undervaluation has proved important to offset the market failures and poor institutional environment that severely hit the dynamic non-resource-intensive traded sectors. This third chapter shows that services sectors in resource-rich MENA countries have been declining as a share of gross domestic product (GDP) and of non-mining GDP as per capita incomes increase. This fourth chapter explores the presence of systematic differences between the patterns of diversification in MENA and the rest of the world. This fifth chapter shows that from a historical perspective, fiscal policy has not contributed significantly to diversification in MENA, because it has been more oriented toward food and fuel subsidies (consumption) rather than toward public goods such as infrastructure (investment). Finally, in this sixth chapter, the authors emphasize the different characteristics of the regional partners in terms of their resource endowments and consider wealth distribution effects within the region.